The development of hepatocellular carcinoma during long-term treatment for recurrent non-small cell lung cancer: a case report - Kang, Seong Hee (Journal of liver cancer, 2023)
Multiple primary malignancies (MPMs) are defined as the presence of two or more malignancies in different organs, without a subordinate relationship. Although rarely reported, hepatocellular carcinoma (HCC) occasionally presents with simultaneous or metachronous primary malignancies in other organs. In this report, we describe a patient with lung adenocarcinoma and lymph node and bone metastases, treated with five chemotherapeutic regimens for 24 months. Changing the chemotherapy regimen based on the suspicion of metastasis of a new liver mass did not lead to improvements. This prompted a liver biopsy and a revised diagnosis of HCC. Sixth-line treatment with the concurrent use of cisplatin-paclitaxel for lung cancer and sorafenib for HCC, stabilized the disease. The concurrent treatment was not tolerated and was discontinued owing to adverse events. Considering our findings, treatment with increased efficacy and lower toxicity for MPMs is warranted.